Dicephalus dipus dibrachius twins: report of an autopsy case - Cristiano Claudino Oliveira; Claudia Aparecida Rainho; Maria Aparecida Custódio Domingues (University of São Paulo, 2014)
Dicephalus dipus dibrachius twins are a rare form of conjoined twins. An autopsy of conjoined dicephalus twins is reported. The diagnosis was performed during the pregnancy and the family received a judicial authorization for termination of pregnancy. The preterm newborn progressed to cardiac arrest and died following a court order to terminate the pregnancy. The conceptus presented two arms, two legs, a trunk, two heads, and a single umbilical cord. The two spinal columns presented vertebral fusion in the sacral region. The heart exhibited complex malformations. The external genitalia were female; and cytogenetic analysis confirmed female sex (46, XX). This analysis also corroborated the etiopathogenic hypotheses described for this abnormality, which proposes failures in embryonic formation rather than specific chromosomal alterations. Current identification of cases by ultrasound permits medical management and multidisciplinary action with the family, enabling the legal termination of pregnancy.